(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
The distribution of responsibilities between different levels of management simultaneously represents the model of the chosen management system. Spain, as well as other unitary states, was affected by the trend of the expansion of the decentralization process. The concept of local self-government, expressed in the European Charter on Local Self-Government, means the right of local authorities to regulate and manage a significant part of public affairs under their responsibility and in the interest of the local population. Assessment of subsidiarity and local independence can be made from a large number of local perspectives. The focus will be on legal, administrative and fiscal aspects between the central and local levels. In the paper, we will analyze the administrative and judicial aspects, with a focus on supervision by the executive and the judiciary, but also the process of fiscal decentralization (distribution of costs, revenues, intergovernmental transfers, and granting of loans). The reason why we chose Spain is that this country has a long history of conflict between centralist and regional-federalist tendencies. The fact is that the complexity of cultural segments with different identities does not correspond to the centralism of the government. That is why the Spanish regional model and the demands for its revision are an important topic that requires a more careful study of the many aspects that this model implies. This paper is not intended to be a comprehensive analysis of Spanish regionalism, but rather a short section of the most significant elements that were actualized after the failed Catalan independence referendum in 2017. For these purposes, the assessment will be made in relation to existing theoretical models and constructions.